PENGARUH FESES KAMBING (Capra aegagrus hircus L.) TERHADAP PENINGKATAN KADAR FOSFAT PADA PUPUK ORGANIK TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq) SEBAGAI SUMBER BELAJAR POSTER - Eka Setia Budi; Agus Sutanto; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
Mesuji is one of the districts that has the largest oil palm plantations in Lampung province. A large amount of Palm Oil Empty Fruit Bunch (TKKS) waste is one of the impacts caused by the extent of the plantation. Oil palm bunches are a fruit stalk and the place where the oil palm fruit attaches. Palm Oil Empty Fruit Bunch (TKKS) is the main waste which is 23% of the palm oil processing. The purpose of this study was to determine the phosphate content of OPEFB organic fertilizer combined with goat feces, determine the comparison that has a good value of phosphate content, and determine the feasibility of the poster making of organic fertilizer for empty palm oil palm bunches (OPEFB) which added goat feces. This type of research is an experiment, using a completely randomized design (CRD). This study used three treatments and one control namely the ratio of Palm Oil Empty Fruit Bunch (TKKS) and goat feces was 1: 0 as a control treatment, 7: 3 as the first treatment, 1: 1 as the second treatment, and 3: 7 as the third treatment. Based on the test results pospat levels obtained an average of each control sample until treatments 1, 2, and 3 are as follows: 0.327%, 0.511%, 0.923%, and 1.330%. The results of one-way ANAVA test analysis found that there was a significant effect of giving goat feces to the OPEFB fertilizer produced and based on ANAVA test results (LSD test) found that the best effect of goat feces was in the third treatment, namely on the comparison of OPEFB feces and goat feces by 3: 7. The results of poster study source validation on the design expert got a value of 86 and the material expert got a value of 95. This study concluded that goat feces affected phosphate levels in OPEFB organic fertilizer, the ratio that had the highest phosphate value was 300 grams of OPEFB and 700 grams of Goat Phases (treatment to goat three), and a poster about the effect of goat feces on phosphate levels in organic fertilizer of oil palm empty fruit bunches is suitable as a learning resource.